Epidermal axonal swellings in painful and painless diabetic peripheral neuropathy. Issue 4 (24th February 2015) - Cheung, Audrey; Podgorny, Peter; Martinez, Jose A.; Chan, Cynthia; Toth, Cory
ABSTRACT: Introduction: The pathophysiology of neuropathic pain (NeP) in diabetic peripheral neuropathy (DPN) is unclear. A potential pathological feature associated with intraepidermal nerve fiber density (IENFD) loss in DPN is axonal swellings. Methods: We determined the prevalence of intraepidermal axonal swellings in DPN patients with or without NeP and compared the findings with diabetes patients without DPN, patients with idiopathic neuropathy with NeP, and control subjects. The primary outcome measure was the ratio of axonal swellings to IENFD. Secondary outcome measures included clinical neuropathy severity and assessment for messenger RNA for voltage‐gated sodium and calcium channels. Results: IENFD was depressed in DPN (with/without pain) and in idiopathic neuropathy patients. Axonal swelling ratios were similar for DPN subjects with and without pain. There was no overexpression of voltage‐gated ion channels in epidermis from DPN patients. Clinical neuropathy severity was only related to IENFD. Conclusions: There was no clinical relationship to pain or clinical neuropathy severity for axonal swellings in DPN. Muscle Nerve 51: 505–513, 2015